121k views
4 votes
3 (a - 1) + 31 - 11a = 4 ( 2a + 3)

User Ryan Davis
by
4.6k points

2 Answers

5 votes

Question :-

3 ( a - 1 ) + 31 - 11a = 4 ( 2a + 3 )

____________________

Solution :-

Given Information :-

  • Equation ➢ 3 ( a - 1 ) + 31 - 11a = 4 ( 2a + 3 )

To Find :-

  • The value of 'a'

Calculation :-

⇒ 3 ( a - 1 ) + 31 - 11a = 4 ( 2a + 3 )

Opening the brackets and multiplying the terms, We get,

⇒ 3a - 3 + 31 - 11a = 8a + 12

⇒ -8a + 28 = 8a + 12

⇒ 8a + 8a = - 28 - 12

⇒ 16a = 40

Transposing 16 to Right Hand Side, We get,

⇒ a =
\sf (40)/(16)

⇒ a =
\sf (-2)/(5)

____________________

Final Answer :-

  • The value of 'a' is
    \bf (-2)/(5)

____________________

User Saquana
by
5.2k points
3 votes

Answer:

-⅖

Explanation:

We need to simplify the given equation and find out the value of a , as ,

=> 3(a-1)+31-11a = 4(2a+3)

=> 3a -3+31-11a = 8a + 12

=> -8a -28 = 8a + 12

=> 16a = -28-12

=> 16a = -40

=> a = -2/5

Hence the value of a is - .

User FkYkko
by
4.5k points